Dental health in children of senior school age with functional pathology of pancreas: interdisciplinary character of the problem - I.S. Lembryk (Zaslavsky O.Yu., 2015)
60 children of senior school age with functional pathology of pancreas and 30 apparently healthy children of the same age were examined for the purpose of dental health assessment. Risk factors of development of lesion of pancreas were detected: irregular nutrition (41.7 %), burdened heredity (33.3 %), autonomic imbalance, in particular instability of vascular tone (13.3 %), massive helminth invasion (11.7 %). There were established the clinical peculiarities of lesions of the pancreas as well as signs of edema of the head of pancreas by data of sonographic method of examination. Factors of deterioration in the condition of oral cavity, teeth and periodontal tissue in the cohort of patients are: unsatisfactory hygiene of oral cavity (absence of a toothbrush, undurable and unthorough brushing of teeth and tongue, inability to use dental floss for removal of uneaten food from gingival sulcus and spaces between teeth), as well as rare visits to a dentist with the purpose of prevention and treatment (46.7 %).